Trwała utrata wartości środków trwałych - znaczenie pragmatyczne, semantyczne i syntaktyczne - Łakomiak, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The author's intention is to point out that the term "permanent loss of capital value" is unsuitable. If it can be the reversal of the loss of capital assets value, it cannot be qualified as permanent. The author shows the definition of value. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 174-183